2007
DOI: 10.1080/10976640701317028
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Muscle Bioenergetics in the Marfan Syndrome Indicates Reduced Metabolic Efficiency

Abstract: The higher EC measured in patients with Marfan syndrome was supported by both oxidative and anaerobic metabolic pathways, thereby suggesting a decrease in muscle efficiency and/or muscle mass, as previously described in other diseases affecting skeletal muscle function such as heart failure and peripheral vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…First, tissue Doppler imaging has demonstrated systolic and diastolic left ventricular dysfunction in Marfan syndrome patients without echocardiographically evident left-sided valvular dysfunction. 6 Second, as generally observed in CHF patients, skeletal muscle from Marfan syndrome patients is thermodynamically inefficient, with a lower ratio of work to energy consumption. 7 Several previous articles have described OHT in patients with Marfan syndrome.…”
Section: Discussionmentioning
confidence: 98%
“…First, tissue Doppler imaging has demonstrated systolic and diastolic left ventricular dysfunction in Marfan syndrome patients without echocardiographically evident left-sided valvular dysfunction. 6 Second, as generally observed in CHF patients, skeletal muscle from Marfan syndrome patients is thermodynamically inefficient, with a lower ratio of work to energy consumption. 7 Several previous articles have described OHT in patients with Marfan syndrome.…”
Section: Discussionmentioning
confidence: 98%
“…The second possible mechanism of HRV suppression derives from the study of affected skeletal muscle function in MS patients. The decreased efficiency of an energy supply within the muscle cells was documented [20]. The study of biventricular dysfunction in MS by cardiac magnetic resonance revealed that it is an intrinsic feature not related to aortic elasticity or b-blocker usage [21].…”
Section: Discussionmentioning
confidence: 99%
“…The high resting lactate concentrations in patients with Marfan syndrome was expected, especially among those who were under β-blocker therapy; two possible explanations acting either independently or simultaneously are offered: the important changes in ventricular performance seen in patients with Marfan syndrome, such as a reduced ejection fraction, an increase in end-systolic volume, and a reduction in systolic contraction velocity, 5,25 combined with vascular abnormalities and endothelial dysfunction 26 could result in low muscle perfusion and an increase in lactate concentrations during physical exercise; and the frequent muscle weakness, muscle fatigue, and myalgia in patients with Marfan syndrome, 27,28 together with the high energy expenditure of skeletal muscles in Marfan patients, result in greater activity in oxidative and anaerobic energy pathways, leading to a higher production of lactate. 29 Heart rate recovery Heart rate recovery has been used as a predictor of mortality and autonomic disorders in cardiovascular diseases. 10,[12][13][14] Although this measurement does not have the same specificity as other evaluation methods of the autonomic nervous system, it strongly correlates with markers of parasympathetic activity in the early phases of recovery as well as markers of sympathetic activity in the late phases of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The high resting lactate concentrations in patients with Marfan syndrome was expected, especially among those who were under β-blocker therapy; two possible explanations acting either independently or simultaneously are offered: the important changes in ventricular performance seen in patients with Marfan syndrome, such as a reduced ejection fraction, an increase in end-systolic volume, and a reduction in systolic contraction velocity, 5 , 25 combined with vascular abnormalities and endothelial dysfunction 26 could result in low muscle perfusion and an increase in lactate concentrations during physical exercise; and the frequent muscle weakness, muscle fatigue, and myalgia in patients with Marfan syndrome, 27 , 28 together with the high energy expenditure of skeletal muscles in Marfan patients, result in greater activity in oxidative and anaerobic energy pathways, leading to a higher production of lactate 29 …”
Section: Discussionmentioning
confidence: 99%